2004
DOI: 10.1080/00087114.2004.10589420
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive DNA sequences as probes for phylogenetic analysis in Vicia genus

Abstract: -In the process of further characterizing phylogenetic relationships among Vicia species of the subgenus Vicia, four different molecular DNA markers were used: a tandemly repeated DNA sequences about 60 bp in length (FokI), a 336 bp element (pVf7) homologous to the IGS repeats (but that does not reside in the policistronic rDNA units); a family of repeated DNA sequences (VfB) of about 1200 bp in length (that might be derived from a mobile DNA element) and a family of repeated DNA sequences (VfM) of about 60 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The high economic importance of the genus Vicia has led to a large body of studies on the molecular characterization and investigation of phylogenetic relationships among species that belong to this genus. Various studies have been reported for investigation of phylogenetic relationships among species based on rDNA (Raina and Ogihara 1995), in situ hybridization with repetitive sequences (Navratilova et al 2003), RAPD analysis (Haider et al 2000;Sakowicz and Cieslikowski 2006), repetitive DNA sequences as probes (Frediani et al 2004), capillary electrophoresis (Piergiovanni and Taranto 2005), and SDS-PAGE on seed storage proteins (Mirali et al 2007). However, none of these could resolve the taxonomic problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high economic importance of the genus Vicia has led to a large body of studies on the molecular characterization and investigation of phylogenetic relationships among species that belong to this genus. Various studies have been reported for investigation of phylogenetic relationships among species based on rDNA (Raina and Ogihara 1995), in situ hybridization with repetitive sequences (Navratilova et al 2003), RAPD analysis (Haider et al 2000;Sakowicz and Cieslikowski 2006), repetitive DNA sequences as probes (Frediani et al 2004), capillary electrophoresis (Piergiovanni and Taranto 2005), and SDS-PAGE on seed storage proteins (Mirali et al 2007). However, none of these could resolve the taxonomic problems.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important is the role of legumes to sustainable agriculture, because of their ability to fix soil nitrogen via symbiotic nitrogen-fixation. They also play an important role as a rotation crop with cereal grain and vegetable crops (Arianoutsou and Thanos 1996;Velazquez et al 2010) The genus Vicia L. is a member of the legume tribe Vicieae of the subfamily Papilionoideae (Frediani et al 2004). The temperate and herbaceous genus Vicia L. comprises 210 annual or perennial species that are widely distributed in temperate regions of Europe, Asia, and the Americas (Maxted 1993;Jaaska 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Vicia L. is a member of the legume tribe Fabeae (sometimes referred to as “Vicieae”) of the subfamily Papilionoideae [1]. Vicia L. comprises approximately 210 species that are widely distributed in temperate regions of Europe, Asia, and the Americas [2].…”
Section: Introductionmentioning
confidence: 99%
“…Relationships among species of the different sections of Vicia have been studied by phenetic analysis of morphological characters (Maxted et al 1991;Maxted 1993Maxted , 1994Maxted , 1995Ohashi 1995, 1997;Maxted and Douglas 1997;Jaaska and Leht 2007;Leht 2009), by isozymes (Jaaska 1997;Leht and Jaaska 2002;Jaaska 2005, Jaaska andLeht 2007), by electrophoretic seed globulin and albumin patterns (Zimniak- Przybylska and Przybylska 1995;Przybylska and Zimniak-Przybylska 1997) and by DNA sequences analyses (Fennell et al 1998;Potokina et al 1999; Van de Wouw et al 2001Frediani et al 2004;Choi et al, 2006;Endo et al 2008). …”
Section: Introductionmentioning
confidence: 99%